Forest-savanna boundary shift on the plateau of Serra Sul dos Carajás (southeastern Amazonia) since the mid-Holocene; driving forces and limiting factors. (25th August 2017) - Alizadeh, Kamaleddin; Matthias, Isabelle; Rodríguez-Zorro, Paula A.; Hermanowski, Barbara; da Costa, Marcondes Lima; Behling, Hermann
Abstract: The vegetation history of the savanna on the plateau of Serra Sul dos Carajás (PSSC) is well studied by three palynological records. Nonetheless there is no record from the forests around this plateau so that the long term forest-savanna boundary shift can be investigated. In this study, a sediment core taken from the forests on the slopes of the plateau is studied using a multi-proxy analysis. The palynological result is compared with the records from adjacent savanna. This study reveals that well-established forests have been present around the plateau during the last 6600 cal yr BP. Since the mid-Holocene owing to a change to favorable climatic conditions, forests started to move toward the savanna and after 3400–4000 years reached their modern borders in the savanna region. Because during this long period forest borders moved horizontally a relatively short distance (ca. 250 m), we concluded that there might be limiting factors that delayed forest expansion. Among different possible factors, fire and human may play an important role. However, the evidence suggests that the slow process of soil formation to produce a soil layer with sufficient depth is the main limiting factor that delayed the forest expansion. According to the previous hydroclimatic and palaeo-ecological studies, the southward displacement of Inter Tropical Convergence Zone (ITCZ) is more likely the trigger of forest expansion in the area since the mid-Holocene.